Study on the Effect of Enzyme and Methionine on Growth Performance and Hemato-Biochemical Parameters in Broilers - Haque, M.E; Mustari, A; Rahman, M.M (Journal of Minerals and Materials Research, 2014)
The experiment was conducted on “Cobb 500” broiler chicks to evaluate the effect of enzymes and methionine supplementation on body weight gain, some hematological parameters (TEC, Hb content, PCV and ESR) and some biochemical parameters (AST and ALT). A total of twenty days old broilers were randomly divided into four equal groups (5×4) as A, B, C and D. Group A was considered as control, fed only with commercial ration, and other (B, C and D) were treated as treatment group, as group B with 1 gm enzymes per liter of drinking water, group C with 1 ml methionine per liter of drinking water and in group D 1 gm enzyme plus 1 ml methionine per liter of drinking water respectively from 0 to 21 days of experiment. It was observed that enzymes and methionine supplementation significantly (P<0.01) increased body. TEC and Hb content increased significantly (p<0.01) in the treated groups as compared to that of control group. ESR, AST and ALT values decreased significantly (p<0.01) in the treated groups from that of the control groups. Therefore, it may be concluded that enzymes and methionine may be used with water to get best result in terms of body weight gain and blood profiles without any detrimental effects on broilers.